Systematic literature review of evaluation of quality management practices in palm oil supply chain: the case of upstream / Muhammad Faizrien Shah Abdul Ghani - Abdul Ghani, Muhammad Faizrien Shah (Faculty of Plantation and Agrotechnology, 2018)
Malaysia is classified among the world’s leading producer and exporter of palm oil. A statistic recorded at 2016 indicates that the total oil palm planted area in Malaysia have reached 5.74 million hectares. In previous findings, the palm oil industry are linked together from upstream to downstream and consists of four sub-sectors which are growers, millers, refiners, and oleo chemicals. However, some organization has yet develop a tool to assess quality management practices in the upstream activity. Besides, the quality management practices implemented has not been so effective. There are various quality management practices that are currently being implemented in palm oil industry. This research attempts to identify the current quality management practices in palm oil upstream supply chain and to develop an instrument to produce quality palm oil in upstream sectors. This paper presents a systematic review on quality management practices in upstream sectors and the final selection comprehends 32 articles selected and comprehensively analyzed to assess quality management practices in upstream processes of palm oil supply chain and finally producing an oil palm quality management tool in the form of checklist.